ANALISIS PENENTUAN HASIL PERTANDINGAN KEJUARAAN GRUP DALAM PERTANDINGAN SEPAK BOLA MENGGUNAKAN METODE BUBBLE SORT PADA STRUKTUR DATA (STUDI KASUS KLASEMEN GRUP C KEJUARAAN SEPAK BOLA EROPA UEFA 2012 - . Nurasiah (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2015)
ABSTRACTThe game of football is universal (general) which has long been known and widely played country any part ofthe world. UEFA European Football Championship in 2012, or better known as Euro 2012, becoming thenational football championship team among the 14 European countries organized by UEFA. purpose of thisstudy is to provide information on the final standings in the group matches of a football match and sequenceposition based on points that have been earned by the team squad. Make it easy to predict as well as groupwinners in the game of football. dal develop an application which can provide information on the finalstandings of the game and which teams are the group winners, runners-up, third and fourth place in a soccergame